2013
DOI: 10.2174/1874325001307010169
|View full text |Cite
|
Sign up to set email alerts
|

Intrapelvic Dislocation of a Femoral Trial Head During Primary Total Hip Arthroplasty Requiring Laparotomy for Retrieval

Abstract: Background and Purpose:Total hip arthroplasty (THA) is a safe and reliable surgical procedure. However, THA also has intra- and postoperative complications. A dreaded and frustrating intraoperative complication during total hip arthroplasty is dislocation of the femoral trial head from the neck into the pelvis.Methods:Here, we report on the case of a 71-year old female patient with osteoarthritis of the left hip. Total hip arthroplasty was performed in a lateral position through a standard posterior approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 9 publications
0
28
1
Order By: Relevance
“…Despite great clinical outcomes and patient satisfaction rates [20] , intraoperative complications during THA are not uncommon, occurring in approximately 5.4% of cases, with femur fractures occurring most commonly [21] . Trial femoral head dislocation into the retroperitoneum is a much rarer complication with limited previous reports ( Table 2 ) [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Although the overall occurrence rate is undetermined, the incidence of this complication at our institution for 34,198 primary THAs from 1998 to present was extremely rare at 0.01%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite great clinical outcomes and patient satisfaction rates [20] , intraoperative complications during THA are not uncommon, occurring in approximately 5.4% of cases, with femur fractures occurring most commonly [21] . Trial femoral head dislocation into the retroperitoneum is a much rarer complication with limited previous reports ( Table 2 ) [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Although the overall occurrence rate is undetermined, the incidence of this complication at our institution for 34,198 primary THAs from 1998 to present was extremely rare at 0.01%.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is one of the most successful and cost-efficient procedures in medicine; however, complications may occur up to 22% [1] , [2] , [3] , [4] . Dislodgement of trial femoral heads and migration into the pelvis is a rarely reported complication with only 14 published cases [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Although a handful of reports are described in the literature, the true incidence of this complication is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Patients understandably will be concerned by the idea of leaving the component in place, however education regarding the potential complications of retrieval including hernia, neurovascular injury, or urologic injury should be discussed. Retrieval of trial femoral heads entrapped in the pelvis may be performed through a separate surgical approach at the time of surgery [3,5,13]. One study regarding leaving trial femoral heads that have become entrapped intrapelvically did not identify adverse effects, and patients have remained asymptomatic when such implants have been left in an intrapelvic position [2].…”
Section: Discussionmentioning
confidence: 99%
“…Citak et al 3 performed laparotomy in order to retrieve the trial head although there are reports of a potentially less invasive laparoscopic retrieval in the setting of the abdominal cavity localisation 10. We favour laparotomy over any kind of laparoscopic solution because of two reasons.…”
Section: Discussionmentioning
confidence: 99%